Exposure to cow’s milk as a prognostic factor for atopic dermatitis during the first three months of life - Widyanti, Putu Ayu; Wati, Ketut Dewi Kumara; Prawirohartono, Endy P. (Paediatrica Indonesiana, 2014)
Background The incidence of atopic dermatitis has increased in the early life of children. Cow's milk, the first foreign protein to which infants are exposed, is predicted to be a prognostic factor of atopic dermatitis. Objective To determine if exposure to cow's milk is a prognostic factor for atopic dermatitis during the first three months oflife. Methods We performed a cohort study involving 136 newborns from families with and without histories of atopy in Sanglah Hospital, Denpasar, between April to August 20 12. Subjects were allocated into 2 groups, those who were exposed to cow's milk (n=68) and not exposed to cow's milk (n=68). We analyzed the impact of several possible prognostic variables on atopic dermatitis at 3 months of age including exposure to cow's milk, birth weight, sex, gestational age, exposure to cigarette smoke, early solid feeding, and history of atopy in the mother, the father, or both, as well as maternal consumption of chicken eggs when nursing. Data were analyzed with Cox's proportional hazard function. The cumulative incidence and incidence rate in each group were calculated. Results Exposure to cow's milk in the first 3 months of life resulted in a cumulative incidence of atopic dermatitis of 17 .6%, with an incidence rate of atopic dermatitis of 54.5%. However, multivariate analysis showed that cow's milk exposure was not a significant prognostic factor for atopic dermatitis (HR 1.3 7; 95%CI 0.22 to 8.43). Conclusion Cow's milk exposure is not a prognostic factor of atopic dermatitis during the first three months of life